ROS 2017
DOI: 10.20455/ros.2017.839
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Mitochondrial Mass by Flow Cytometry during Oxidative Stress

Abstract: Properly assessing mitochondrial health is crucial to understand their role in disease. MitoTracker green (MTG) and nonylacridine orange (NAO) are fluorescent probes which have been commonly used to assess mitochondrial mass. This is based on the assumption that both MTG and NAO accumulate in mitochondria regardless of the mitochondrial transmembrane potential (ΔΨm). Here, we utilized flow cytometry to evaluate the performance of these probes for assessment of mitochondrial mass relative to forward (FSC) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 10 publications
6
50
0
Order By: Relevance
“…RNA-seq analysis confirmed that Tnnt2 low (Mitotracker high ) cardiomyocytes do express a slightly lower level of Tnnt2 mRNA as compared to Tnnt2 high (Mitotracker low ) cardiomyocytes. Although Mitotracker staining level is high, mitochondrial gene expression level was lower in Tnnt2 low (Mitotracker high ) cardiomyocytes than Tnnt2 high (Mitotracker low ) cardiomyocytes in WT heart, suggesting that Tnnt2 low (Mitotracker high ) cardiomyocytes represent relatively immature cardiomyocytes and that Mitotracker does not reflect the functional maturity of mitochondria in this context, consistent with previous observations [17][18][19] .…”
Section: Two Distinct Cardiomyocytes Populations In Neonatal Heartssupporting
confidence: 90%
See 1 more Smart Citation
“…RNA-seq analysis confirmed that Tnnt2 low (Mitotracker high ) cardiomyocytes do express a slightly lower level of Tnnt2 mRNA as compared to Tnnt2 high (Mitotracker low ) cardiomyocytes. Although Mitotracker staining level is high, mitochondrial gene expression level was lower in Tnnt2 low (Mitotracker high ) cardiomyocytes than Tnnt2 high (Mitotracker low ) cardiomyocytes in WT heart, suggesting that Tnnt2 low (Mitotracker high ) cardiomyocytes represent relatively immature cardiomyocytes and that Mitotracker does not reflect the functional maturity of mitochondria in this context, consistent with previous observations [17][18][19] .…”
Section: Two Distinct Cardiomyocytes Populations In Neonatal Heartssupporting
confidence: 90%
“…Tnnt2 high and Tnnt2 low cardiomyocytes were Mitotracker low and Mitotracker high , respectively. As the Mitotracker does not necessarily reflect the mitochondrial function [17][18][19] , we examined the mRNA expression signature of Tnnt2 high and Tnnt2 low cardiomyocytes genome-wide. To collect the cells alive, two populations were sorted from MHC-Cre tg ; R26 +/YFP reporter hearts in both WT and Glut1 transgenic background using YFP reporter and Mitotracker ( Fig.…”
Section: Two Distinct Cardiomyocytes Populations In Neonatal Heartsmentioning
confidence: 99%
“…Furthermore, a significant enrichment of TFH development pathways was found in CD57 hi compared to CD57 lo TFH cells (Supplemental Figure 3B) underlined by the higher expression of TOX2 (Supplemental Figure 2C), a positive regulator for TFH cell development (23). Ex vivo flow cytometry analysis (Supplemental Figure 3D), showed a significantly increased binding of TMRE (a marker for mitochondrial membrane potential (24)) and Mitotracker green FM (a surrogate for "mitochondrial mass" (25)) in TFH compared to non/pre-TFH cells ( Figure 2E), consistent with their pathway signatures (Supplemental Figure 3A). A significant difference was also found for TMRE binding between CD57 lo and CD57 hi TFH cells ( Figure 2E).…”
Section: Unidirectional Transition Form Cd57 Lo Pd-1 Hi To Cd57 Hi Pdmentioning
confidence: 95%
“…The basic mechanism is that the accumulation of this NAO dye in the mitochondrial membrane and to alter the trans-membrane potential as well. NAO can present in mitochondria, where it binds to cardiolipin [33]. The result in terms of average fluorescence unit (FU) in mitochondrial mass content among different groups is shown in Figure 2.…”
Section: Mitochondrial Mass Contentmentioning
confidence: 96%